Exorbitant Privilege: A Safe-Asset View - Zhengyang Jiang (CESifo GmbH, 2024)
I propose a model of the reserve currency paradigm that centers on liquidity demand for safe assets. In global recessions, the demand for U.S. safe assets increases and raises their convenience yields, giving rise to stronger dollar and countercyclical seigniorage revenues. The seigniorage revenues raise the U.S. wealth and consumption shares in recessions, despite the U.S. suffering portfolio losses from external positions. This asset demand channel also connects exchange rates to bond holdings, which provides new perspectives on exchange rate disconnect and the exchange rate-capital flow relationship. Under this safe-asset view, exorbitant privilege does not require exorbitant duty.
Keywords: E44; F32; G15; 330; exorbitant privilege; reserve assets; international monetary system; capital flows